The Impact of Applying High Intensity Interval Training with Integrated Volume on Improving the Endurance Athletes - Kanzha Dilla Davina; Dikdik Zafar Sidik; Fitri Rosdiana (Gladi : Jurnal Ilmu Keolahragaan, 2026)
Abstract This study to ascertain how Tarung Derajat athletes' endurance was affected by using the High Intensity Interval Training technique with integrated volume. An experimental strategy using a One Group Pre-test Post-test Design was the research methodology employed. Eight athletes who met the inclusion criteria West Java SPOBDA athletes who had competed in multiple provincial championships and the exclusion criteria adults without any competitive experience and athletes who were currently injured were included in the research sample, which was selected using a total sampling technique. This study's lack of a control group makes it more difficult to establish a clear relationship. Nonetheless, the findings provide initial empirical evidence that Tarung Derajat athletes' endurance may be improved by doing High Intensity Interval Training with Integrated Volume. The Multi-stage Fitness Test was the test tool utilized. There were ten training sessions during the course of the four-week program. Utilizing the concept of progressive overload in conjunction with an integrated volume approach that integrates exercise time and intensity in each session. Data analysis included descriptive statistics, normality tests, homogeneity tests, and hypothesis testing with paired sample t-tests. The average VO₂max value increased from 44.26 to 51.05 in the post-test. The hypothesis test results showed a significance value of 0.000 (p < 0.05), indicating that the application of the High Intensity Interval Training approach with integrated volume increased the endurance of Tarung Derajat athletes. Thus, it can be concluded that the High Intensity Interval Training program with integrated volume increased the cardiovascular endurance of athletes.